Tenosynovial giant cell tumour (diffuse type) with a background of malignant melanoma: a case report from South Africa - Rushern Ruvashin Chetty; Sanele Kunene (Journal of Current Oncology and Medical Sciences, 2025)
Introduction: Tenosynovial giant cell tumour (TGCT) is a rare mesenchymal tumour that affects joints and tendon sheaths, little is known about conditions associated with TGCT. Case Presentation: Mr X, a 89-year-old male, known with a history of malignant melanoma was initially thought to have metastatic lung lesions from the melanoma. Following a lung biopsy, Mr X was diagnosed with a second primary lesion – TGCT: diffuse type – rather than a metastatic lesion. The patient was not considered for referral to a multidisciplinary sarcoma team due to the advanced stage of disease. Mr X deteriorated and demised after commencing Imatinib. Discussion: Although one would think that a pulmonary lesion in a patient with a history of cancer is metastatic disease, it is not always the case. The patient may have two primary cancers that are unrelated. One other case report has previously been published on a patient with a TGCT and Melanoma. Conclusion: TGCT is a rare condition that may or may not be associated with melanoma. We recommend that suspected metastatic melanoma lesions be biopsied to establish or refute this association.